A Comparative Study of Metaphors about Women between Thai and Chinese Languages on the Internet - Pan, Yongxing (Interdisciplinary Academic and Research Journal, 2023)
Humans have two biological sexes: male and female. However, the view of women is partly the result of society and culture in Thai society and Chinese society in the past, which had different views of women than men, which was reflected in the use of language. Thus, this article aims to compare metaphors about women between Thai and Chinese on Internet and the thoughts about women in both Thai and Chinese reflected in these metaphors studied. The data was collected from www.Pantip.com and www.Weibo.com. It was found that both Thai and Chinese have three major types of metaphors. There were animate, inanimate metaphors, and natural metaphors. And both languages have eight subtypes of metaphors are the same, including 1) animate metaphors, namely human-related metaphors, plant-related metaphors, and animal-related metaphors 2) inanimate metaphors, namely food-related metaphors, object-related metaphors, product-related metaphors, machine-related metaphors, and natural metaphors. There are four subtypes of metaphors only in the Thai language or Chinese language, including property-related metaphors, disease-related metaphors, medicine-related metaphors, and building-related metaphors.